Digital Divide: Geotechnology, Politics and the International System - Wong, Johnson (Université d'Ottawa | University of Ottawa, 2020)
The international order is undergoing a transformation with much of it being driven by technological innovation. While states jostle for position in this modern global hierarchy, new and old alliances are forming along two strategic streams: On one side are mostly Western democratic countries led by the United States, and the other side consists of autocratic and illiberal states led by China and Russia. Whereas the incentives of globalization and capitalism will compel states to cooperate economically, this new order will be politically and digitally divided. Not only will this irrevocably alter the liberal international system that has dominated the last 50 years, it will tip the balance of power in favour of regional hegemons. While this major research paper will show that the continued era of an American-led liberal international order may be uncertain, there are still powerful institutional pressures that could intervene and influence the trajectory of history.